Right-Natural Aspect of the Right to Submit Complaints and Requests - Kazimierczuk, Marcin (Studia Warmińskie, 2019)
Guaranteed to everyone in art. 63 of the Constitution of the Republic of Poland gives the right to lodge complaints and motions when the public authorities and social organizations or institutions perform tasks entrusted to them in a way that does not meet the expectations of those directly involved. They are a valuable source of information on the relationship of individuals to public bodies, especially in areas that need to be optimized. These are primarily the basic tools by which individuals try to actualize their rights. The purpose of this article is to present, in addition to the sources of positive law established by state authorities, also the right-natural ground from which an institution of complaints and conclusions arises.